Microbiological and clinical effects of a dentifrice containing zinc citrate and Triclosan in the human experimental gingivitis model - Jones, C L; Saxton, C A; Ritchie, J A (Journal of clinical periodontology, 1990)
A partial mouth experimental gingivitis model was employed to establish the effect of a dentifrice containing 0.2% Triclosan and 0.5% zinc citrate on the development of chronic gingivitis. In addition, changes in the plaque flora associated with the developing gingivitis have been monitored. Following a period of stringent oral hygiene, volunteers were allocated to 1 of 2 treatment groups. A toothshield was constructed to fit 4 posterior mandibular teeth. During the 21-day experimental period test or placebo dentifrice was applied to the experimental teeth via the tooth shield. The toothshield also prevented plaque removal from those teeth during habitual brushing of the remaining dentition. Supragingival plaque was collected at baseline and day 21 for analysis of the total bacterial flora. At the end of the experimental period, plaque and gingivitis had developed in both groups. However, the test group had significantly less plaque and gingivitis than the placebo group. The microbiological data demonstrated that plaque from the test group contained significantly lower numbers of anaerobes compared to plaque from the placebo group. This was considered particularly significant as these bacteria are generally associated with chronic inflammatory periodontal disease. There was also a trend for the numbers of actinomyces to decrease in plaque from the test group but not in the placebo group.